P-wave velocity in ultrahigh temperature granulites from the Archean Napier Complex, East Antarctica - Shingai, Eisuke; Ishikawa, Masahiro; Arima, Makoto (National Institute of Polar Research, 2001)
P(論文) P-wave velocities (Vp) in ultra-high temperature granulites (UHT) were measured up to 1.0 Gpa from 25°C to 400°C with a piston-cylinder-type high-pressure apparatus. Rocks measured are meta-igneous UHT rocks collected from Mount Riiser-Larsen, Amundsen Bay, Napier Complex. Core rock samples 14 mm in diameter and 12 mm long were subjected to high-pressure experiments. All rocks show a rapid increase of Vp at low pressure up to 0.5 Gpa and nearly constant Vp at higher pressures. The Vp values measured at 1.0 Gpa and 400°C are 7.17 km/s for a metapyroxenite, 6.93 km/s, 6.88 km/s for mafic granulites and 6.17 km/s for an orthopyroxene felsic gneiss. A well-defined correlation exists between Vp and the SiO_2 content of the rocks, which is expressed as Vp (km/s)=-0.051SiO_2+9.85 at 1.0 Gpa and 25℃. The Vp values measured for the Napier mafic granulites are comparable to those of the Mizuho lower crustal layer (6.95 km/s of Vp at depth from 33 to 40 km; A. Ikami et al, Mem. Natl Inst. Polar Res., Ser. C, 15, 69, 1984). The present results suggest that the lower crust in the Mizuho Plateau is probably composed of mafic granulites (garnet-free) rather than garnet-bearing rocks. The higher pressure in Liitzow-Holm Complex overlie the lower pressure rocks (Napier Complex). The double-thickened crustal model in which peak metamorphic pressure increases with depth can't explain the inversion of metamorphic pressure across the crust. We suggest that the Liitzow-Holm Complex was exhumed tectonically upon the Napier Complex after the Pan-African continental collision between the Napier Complex and Dronning Maud Land. departmental bulletin paper